2014
DOI: 10.1007/s00345-014-1288-3
|View full text |Cite
|
Sign up to set email alerts
|

Is there an anti-androgen withdrawal syndrome for enzalutamide?

Abstract: If existent, an AAWS is at least very rare for enzalutamide in patients with mCRPC after taxane-based chemotherapy and does not play a clinical role in this setting. This may be attributed to the different pharmacodynamics of enzalutamide. Longer duration of therapy or a longer withdrawal interval may reveal a rare EWS in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Unfortunately, no factors were found to be adequate predictors of response. In the second study, von Klot and coworkers reported the occurrence of EWS in 31 patients whose data were collected from 6 different centers in Germany (von Klot et al 2014). No PSA reduction was observed in any of the 31 patients, and authors concluded that if existent, an EWS was at least very rare for enzalutamide in patients with mCRPC after taxane-based chemotherapy and without a clinical role in this setting.…”
Section: Enzalutamide Withdrawal Syndrome (Ews)mentioning
confidence: 99%
“…Unfortunately, no factors were found to be adequate predictors of response. In the second study, von Klot and coworkers reported the occurrence of EWS in 31 patients whose data were collected from 6 different centers in Germany (von Klot et al 2014). No PSA reduction was observed in any of the 31 patients, and authors concluded that if existent, an EWS was at least very rare for enzalutamide in patients with mCRPC after taxane-based chemotherapy and without a clinical role in this setting.…”
Section: Enzalutamide Withdrawal Syndrome (Ews)mentioning
confidence: 99%
“…Im Gegensatz zu anderen Antiandrogenen wie Bicalutamid hat Enzalutamid keine agonistische Wirkung. In diesem Zusammenhang wird die Frage eines Enzalutamid Withdrawal Syndroms (EWS) für dieses neue Antiandrogen kontrovers diskutiert: In vitro, in vivo sowie klinische Daten sprechen für das mögliche Vorliegen eines EWS, welches allerdings in dem bisher untersuchten Setting nach Chemotherapie in weniger als 10 % der Fälle vorkommen dürfte und derzeit klinisch keine Relevanz hat [6,7]. In der AFFIRM- …”
Section: Enzalutamidunclassified
“…It has previously been described for antiandrogens such as flutamide and bicalutamide, but information regarding enzalutamide withdrawal is currently limited von Klot et al 2014avon Klot et al , 2014b. Two recent reports, based on 30 patients and 31 patients with mCRPC, respectively, suggest that antiandrogen withdrawal syndrome with enzalutamide appears to be rare with the Datapoints are means and whiskers depict standard deviations.…”
Section: Other Observationsmentioning
confidence: 99%
“…Adverse event, n (%) Enzalutamide (n = 800) Placebo (n = 399) currently available follow up and withdrawal timeframes [Phillips, 2014;Rodriguez-Vida et al 2014;von Klot et al 2014a].…”
Section: Other Observationsmentioning
confidence: 99%